Analisis Teologis dengan berbagai sumber untuk mempertimbangkan praktek Gereja Rumah bagi lansia pasca covid 19 - Delila Tanaem (Peneliti.net, 2021)
In 2019, the case of Covid 19 (corona virus) became a global pandemic, including in Indonesia. The government and the Church in Indonesia responded by doing social distancing with an appeal to congregation members to worship at home. This is an experience that refreshes the faith of the elderly who have not been able to reach the Church due to physical decline, but because of the decrease in the death rate the Church can return to church in the Church. This then creates a dilemma among the elderly because the church has to return to the church building, so the physically limited elderly can no longer go to church because the house church has been completed. The purpose of this study is to provide theological considerations with various sources to consider the practice of house churches for the elderly after Covid 19. The method used is hermeneutics on the implementation of house churches as well as physiological and psychological analysis of the elderly. The result of this research is that house churches are a new thing in the Christian world, because the prototype according to the Bible can be found in the worship patterns of the early church initiated by the Apostles. And the house church concept answers the needs of the elderly who have not been able to go to church for so long because of decreased physical abilities and psychological changes. Thus the House Church can be an option for the Church to make it a special Church program to answer the spiritual needs of the elderly who cannot reach the Church after COVID-19 in Indonesia. The Elderly Home Church is very friendly for the elderly.